Experimental and Theoretical (ab initio and DFT) Analysis of UV-Vis Spectra, Thermodynamic Functions and Non-linear Optical Properties of 2-Chloro-3,4-Dimethoxybenzaldehyde - kumar, sarvendra; Kumar, Rajesh; Teotia, Jayant; Yadav, M. K. (JOURNAL OF ADVANCES IN PHYSICS, 2015)
In the present work, UV- Visible spectra of 2-Chloro-3,4-Dimethoxybenzaldehyde (2,3,4-CDMB) compound have been carried out experimentally and theoretically. The ultraviolet absorption spectrum of title compound in three solvents (Acetone, Diethyl Ether, CCl4) of different polarity were examined in the range of 200 500 nm. The structure of the molecule was optimized and the structural characteristics were determined by HF and DFT (B3LYP) methods with 6-31+G(d,p) and 6-311++G(d,p) as basis sets. The excitation energy, wavelength corresponds to absorption maxima () and oscillator strength (f) are calculated by Time-Dependent Density Functional Theory (TD-DFT) using B3LYP/6-31+G(d,p) and B3LYP/6-311++G(d,p) as basis sets. The electric dipole moment (Î¼), polarizability (Î±) and the first hyperpolarizability (Î² ) have been computed to evaluate the non-linear optical (NLO) response of the investigated compound by HF and DFT (B3LYP) with already mentioned basis sets. Thermodynamic functions of the title compound at different temperatures were also calculated.